2005
DOI: 10.1901/jaba.2005.161-02
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Evaluation of Food Textures to Decrease Packing and Increase Oral Intake in Children With Pediatric Feeding Disorders

Abstract: This study examined packing (pocketing or holding accepted food in the mouth) in 3 children who were failing to thrive or had inadequate weight gain due to insufficient caloric intake. The results of an analysis of texture indicated that total grams consumed were higher when lower textured foods were presented than when higher textured foods were presented. The gram intake was related directly to levels of packing. That is, high levels of packing were associated with higher textured foods and low gram intake, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 17 publications
6
71
0
Order By: Relevance
“…The pattern suggests that the increased rate of expulsions that accompanied these higher textures may function as a means to 'escape' higher texture bite presentations due to a skill deficit for handling those textures, as Bob appeared incapable of chewing and swallowing without gagging. This presentation is consistent with the findings of Patel et al (2005), providing additional evidence that deficits in oral motor skills may hinder consumption of higher textures.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The pattern suggests that the increased rate of expulsions that accompanied these higher textures may function as a means to 'escape' higher texture bite presentations due to a skill deficit for handling those textures, as Bob appeared incapable of chewing and swallowing without gagging. This presentation is consistent with the findings of Patel et al (2005), providing additional evidence that deficits in oral motor skills may hinder consumption of higher textures.…”
Section: Discussionsupporting
confidence: 90%
“…Alternatively, Patel, Piazza, Layer, Coleman, and Swartzwelder (2005) suggested that, in some cases, feeding behaviors with topographies similar to refusal behaviors (e.g., expelling; packing) may be the result of oral-motor skill deficits (e.g., poor chewing skills; difficulty with tongue lateralization), rather than food aversion. This assertion was based on the results of an analysis indicating that, among a sample of three children with food refusal, acceptance remained high regardless of the texture at which the food was presented, while packing was associated with higher textures only.…”
mentioning
confidence: 99%
“…Because a large number of children with autism demonstrate food selectivity, future research should focus on the function of selective eating and methods of treatment. For example, function-based assessments could be conducted to extend the work of Munk and Repp (1994) and Patel, Piazza, Layer, Coleman, and Swartzwelder (2005) to determine how bolus size, food type, texture, flavor, color, shape, and utensils influence feeding behavior. Such function-based assessments could be used to prescribe treatments that manipulate relevant variables (e.g., texture) to expand the variety of foods consumed.…”
mentioning
confidence: 99%
“…Another study used fading, differential reinforcement, and escape extinction to increase intake of a calorie-dense fluid consisting of milk and a powder supplement in a 6 year-old boy with ASD (Patel et al 2005). Prior to treatment, the participant accepted water from a cup, but refused other liquids.…”
Section: Liquid Avoidancementioning
confidence: 99%